2008
DOI: 10.1002/jso.21182
|View full text |Cite
|
Sign up to set email alerts
|

End‐to‐end versus end‐to‐side stapled anastomoses after anterior resection for rectal cancer

Abstract: Regarding postoperative surgical complications, end-to-side anastomosis is a safe procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…Only 2 experimental studies matched the inclusion criteria; one study 117 found no significant difference in blood flow between ETE or side-to-side anastomosis after rectal resection in pigs, and the other 118 found better blood flow in ETE compared with side-to-end anastomosis after rectal resection in dogs. The included RCTs are also scarce: one 119 on ETE vs endto-side found more AL in ETE, and the other 120 on the optimum side limb for side-to-end colorectal anastomosis found no significant difference between 3-and 6-cm sized limbs. No studies investigating the ideal length of the enterotomy were identified.…”
Section: Configuration Of Colorectal Anastomosismentioning
confidence: 99%
“…Only 2 experimental studies matched the inclusion criteria; one study 117 found no significant difference in blood flow between ETE or side-to-side anastomosis after rectal resection in pigs, and the other 118 found better blood flow in ETE compared with side-to-end anastomosis after rectal resection in dogs. The included RCTs are also scarce: one 119 on ETE vs endto-side found more AL in ETE, and the other 120 on the optimum side limb for side-to-end colorectal anastomosis found no significant difference between 3-and 6-cm sized limbs. No studies investigating the ideal length of the enterotomy were identified.…”
Section: Configuration Of Colorectal Anastomosismentioning
confidence: 99%
“…L-SST and DST are almost the same anastomoses performed with a circular stapler, except for the dog ear; therefore, this result was reasonable. However, the dog ear and crossing point were previously reported to be potentially vulnerable areas and could also lead to anastomotic leakage [8][9][10]. Furthermore, multiple staplers firing during DST could lead to an excessively long stapling line due to an inadequate cutting angle in many cases, which might contribute to anastomotic leakage [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, DST has some drawbacks such as the lateral intersecting staple lines (the so-called dog ears), crossing point of the staplers, and multiple staplers firing. The dog ear, crossing point, and multiple staplers firing might lead to anastomotic leakage [8][9][10][11][12]. In addition, laparoscopic surgery, especially an intracorporeal operation, is technically more difficult than open surgery due to the width and limited articulation of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The most important surgical complication following rectal resection with anastomosis is symptomatic AL. [3][4][5]11,12 The incidence of AL varies widely depending on the anastomosis type and the distance from the anal verge. Multiple studies have identified distance from the anal verge to be a substantial risk factor contributing to anastomotic breakdown.…”
mentioning
confidence: 99%